Answer:
Since the independent variable x is not the exponent, [tex]y = - 7 x^{8}[/tex] does not represent an exponential function.
Step-by-step explanation:
The general expression of an exponential function is [tex]f(x) = a^{x}[/tex], where a > 0 and a ≠ 1
Now the given function is [tex]y = - 7 x^{8}[/tex] ..... (1)
So, we can say that the function f(x) = y is not an exponential function as x is not in power of any constant.
Therefore, since the independent variable x is not the exponent, [tex]y = - 7 x^{8}[/tex] does not represent an exponential function. (Answer)
Five tenths in standard and expanded form
Answer:
Standard form: 5 x 10^-1
Expanded form: 0.5
Step-by-step explanation:
hope this helps
The graphs below have the same shape. What is the equation of the blue graph?
Answer:
Option C. [tex]g(x)=(x+5)^{2}[/tex]
Step-by-step explanation:
we know that
The equation of the parent function f(x) (red graph) is
[tex]f(x)=x^{2}[/tex]
This is a vertical parabola open upward
The vertex is the point (0,0) (the origin)
The function g(x) (blue graph) is a vertical parabola open upward
The vertex is the point (-5,0)
The transformation of f(x) to g(x) has the following rule
f(x) -----> g(x)
(0,0) ----> (-5,0)
(x,y) ----> (x-5,y)
That means----> The transformation is a translation of 5 units at left
therefore
The equation of g(x) is
[tex]g(x)=(x+5)^{2}[/tex]
solve the inequality and enter your solution as an inequality comparing the variable to the solution
-19>x-26
Answer:
x < 7
Step-by-step explanation:
We are given an equation of inequality and we have to solve the equation as an inequality.
The given equation is - 19 > x - 26
⇒ - 19 + 26 > x
⇒ 7 > x
⇒ x < 7 {Since, if a > b then we can write b < a, as they are equivalent}
Hence,the solution of the equation of the inequality is x < 7. (Answer)
What is 8.4 x 10^12/4.2 x 10^6
Answer:
2 × [tex]10^{6}[/tex]
Step-by-step explanation:
Using the rule of exponents
[tex]\frac{a^{m} }{a^{n} }[/tex] ⇔ [tex]a^{(m-n)}[/tex]
Split the fraction into a product, that is
= [tex]\frac{8.4}{4.2}[/tex] × [tex]\frac{10^{12} }{10^{6} }[/tex]
= 2 × [tex]10^{(12-6)}[/tex]
= 2 × [tex]10^{6}[/tex]
What is the value of the expression if m=3 and n=2?
2(m3) + (6-n)n
Be sure to explain all of the steps you used in solving this problem.
Step-by-step explanation:
So fill it in
2(3 times 3)+(6-2)2
so
2(9)+(4)2
then
18+8=26
Answer: 26
hope that is right
Answer:
First plug in for m and n
2(3)(3) +(6-2)(2)
Next solve
18 + 8
Answer= 10
Step-by-step explanation:
What is the final step in solving the inequality -2(5 - 4x)
Step 1: -10 + 8x < 6x - 4
Step 2: -10 <-2x - 4
Step 3: -6<-2x
Step 4
AVA
Step-by-step explanation:
[tex]-2(5-4x)<6x-4\qquad\text{use the distributive property}\\\\(-2)(5)+(-2)(-4x)<6x-4\\\\-10+8x<6x-4\qquad\text{subtract}\ 8x\ \text{from both sides}\\\\-10+8x-8x<6x-8x-4\\\\-10<-2x-4\qquad\text{add 4 to both sides}\\\\-10+4<-2x-4+4\\\\-6<-2x\qquad\text{divide both sides by (-2)}\\_{\text{by dividing by a negative number, flip the inequality sign}}\\\\3>x[/tex]
find the slope and the y-intercept of y=9x-2
Answer:
The Slope is 9 and the y-intercept is -2
Step-by-step explanation:
Answer: slope=9
Y-intercept=-2
Step-by-step explanation:
Use y=mx+b where m equals slope and b equals y-intercept
A textbook costs $65.49 before tax. The tax on the textbook is 6.5%.
What is the total cost of the textbook?
Round your answer to the nearest cent.
Enter your answer in the box.
Answer:
$69.75
Step-by-step explanation:
Given: Cost of textbook before tax=$65.49
The tax on the textbook = 6.5%
The tax amount = 6.5% of $65.49
=\frac{65}{1000}\times65.49=4.25685\approx4.26
⇒The tax amount = $4.26
The total cost of the textbook=Cost of textbook before tax+tax amount
=$65.49+$4.26
=$69.75
The total cost of the textbook is $69.75.
Credit goes to @JeanaShupp
Answer:
Answer is69.75
Step-by-step explanation:
plz help me plz I will mark brainlest for the person who answer first
Answer:
[tex] \frac{16}{20} [/tex]
Step-by-step explanation:
he sold 16 and he was supposed to sell 20. therefore it's 16/20. not relevant, but he sold 80% of the tickets
Answer:
I don't know why but I personally think its 1/4 I'm probably wrong but I'm trying my best well I hope dis helps and stay safe :3
At a music festival, T-shirts are sold for $15 and sweatshirts are sold for $20. The festival organizers pay x dollars for each T-shirt and y dollars for each sweatshirt. The festival sells 53 T-shirts and 39 sweatshirts.
Write and simplify an expression that represents the profit.
Answer:
38.0
Step-by-step explanation:
you have to you's the part and whole number ≤Answer:
53(15) + 39(20) = x
795 + 780
=1,575
Step-by-step explanation:
there are 53 t-shirts 15$ each. Then 39 sweatshirts each 20$. so 53*15 + 39*20 will be your final solution.
Which three comparisons are true?
1/2 = 2/4
6/8 = 1/4
3/6 = 2/4
2/4 = 4/6
4/8 = 2/4
Answer:
The answer is 4/8=2/4 because 4/8 simplifying is 2/4 or 1/2
The true fraction comparisons are 1/2 = 2/4 and 4/8 = 2/4. The other comparisons are false. Simplifying fractions helps determine their equality.
Comparing Fractions:
Let's determine which of the given fraction comparisons are true:
1/2 = 2/4: To check this, we can simplify 2/4. Dividing both the numerator and the denominator by 2, we get 1/2. Thus, 1/2 equals 2/4. This is a true statement.6/8 = 1/4: We simplify 6/8 by dividing both the numerator and the denominator by 2, which gives us 3/4. This does not equal 1/4. This is a false statement.3/6 = 2/4: Simplifying 3/6 by dividing both the numerator and the denominator by 3, we get 1/2. Simplifying 2/4 gives us 1/2 as well. Therefore, 3/6 equals 2/4. This is a true statement.2/4 = 4/6: Simplifying 2/4 to 1/2 and simplifying 4/6 to 2/3 shows that 2/4 does not equal 4/6. This is a false statement.4/8 = 2/4: Simplifying 4/8 by dividing both the numerator and the denominator by 4, we get 1/2. Simplifying 2/4 also gives us 1/2. Thus, 4/8 equals 2/4. This is a true statement.The three true comparisons are: 1/2 = 2/4, 3/6 = 2/4, 4/8 = 2/4, and none from the rest.
Please help solve with steps: Order of operation with integers.
6 (divide by ) (-3) - (-9)
Answer:
7Step-by-step explanation:
Use PEMDAS:
P Parentheses first
E Exponents
MD Multiplication and Division
AS Addition and Subtraction
[tex]6:(-3)-(-9)[/tex] first - division
[tex]=-2+9[/tex] use commutative property a + b = b + a
[tex]=9+(-2)=9-2=7[/tex]
Karen bought a coat for 20% more than the price she wanted to pay. If she paid $150, how much was she looking to pay?
The first one to get both correct will be brainiest!!!!!!!
120% = $150
divide both sides by 6
20% = $25
We want the regular price, so 100%.
multiply both sides by 5
100% = $125
Answer:125
Step-by-step explanation:
150/1.20
=125
Simultaneous equations !
Who can help
The cost of glass is: £4
The cost of mug = £2
Step-by-step explanation:
Let g be the number of glasses and
m be the number of mugs
[tex]3g+3m = 18\ \ \ \ \ Eqn\ 1\\6g+4m=32\ \ \ \ \ Eqn\ 2[/tex]
Multiplying equation 1 by 2
[tex]6g+6m=36\ \ \ \ Eqn\ 3[/tex]
Subtracting Eqn 2 from Eqn 3
[tex]6g+6m - (6g+4m) = 36-32\\6g+6m-6g-4m=4\\2m=4[/tex]
Dividing both sides by 2
[tex]\frac{2m}{2} = \frac{4}{2}\\m = 2[/tex]
Putting m=2 in eqn 1
[tex]3g+3(2) = 18\\3g+6 = 18\\3g = 18-6\\3g = 12[/tex]
Dividing both sides by 3
[tex]\frac{3g}{3} = \frac{12}{3}\\g = 4[/tex]
Hence,
The cost of glass is: £4
The cost of mug = £2
Keywords: Linear Equation, simultaneous equations
Learn more about linear equation at:
brainly.com/question/2367554brainly.com/question/2670657#LearnwithBrainly
Complete this statement:
45x^3a + 27xa^2= 9xa
Enter the correct answer.
0000
DO
Clear all
DOO
Answer:
[tex]45x^3a+27xa^2= 9xa(5x^2+3a)[/tex]
Step-by-step explanation:
Given:
[tex]45x^3a+27xa^2= 9xa[/tex]
We need to complete this Statement.
By Solving the above equation we get;
We will take some common factor out so we will get;
[tex]45x^3a+27xa^2= 9xa(5x^2+3a)[/tex]
Hence the Complete statement is [tex]45x^3a+27xa^2= 9xa(5x^2+3a)[/tex]
What is the product?
(negative 3 s + 2 t)(4 s minus t)
negative 12 s squared minus 2 t squared
negative 12 s squared + 2 t squared
negative 12 s squared + 8 s t minus 2 t squared
negative 12 s squared + 11 s t minus 2 t squared
Answer:
(d) negative 12 s squared + 11 s t minus 2 t squared is the PRODUCT.
Step-by-step explanation:
Here, the given expression is:
(negative 3 s + 2 t)(4 s minus t) = (- 3s + 2t) (4s - t)
Now, by DISTRIBUTIVE PROPERTY:
A(B-C) = AB - AC
Simplifying the given expression ,we get:
[tex](- 3s + 2t) (4s - t) = -3s(4s-t) + 2t(4s -t)\\= -3s(4s) -3s(-t) + 2t(4s) + 2t(-t) = -12s^2 + 3st + 8 st - 2t^2\\= -12s^2 + 11st - 2t^2\\\implies (- 3s + 2t) (4s - t) = -12s^2 + 11st - 2t^2[/tex]
Now, the resultant expression can also be written as
[tex]-12s^2 + 11st - 2t^2[/tex] = negative 12 s squared + 11 s t minus 2 t squared.
Hence, the option (4) is the correct option.
Answer:
option 4 is the answer
Step-by-step explanation:
over what interval will the immediate value theorem apply
Answer:
Any [a,b] that does NOT include the x-value 3 in it.
Either an [a,b] entirely to the left of 3, or
an [a,b] entirely to the right of 3
Step-by-step explanation:
The intermediate value theorem requires for the function for which the intermediate value is calculated, to be continuous in a closed interval [a,b]. Therefore, for the graph of the function shown in your problem, the intermediate value theorem will apply as long as the interval [a,b] does NOT contain "3", which is the x-value where the function shows a discontinuity.
Then any [a,b] entirely to the left of 3 (that is any [a,b] where b < 3; or on the other hand any [a,b] completely to the right of 3 (that is any [a,b} where a > 3, will be fine for the intermediate value theorem to apply.
2. Use the linear combination method to solve the system of equations. Explain each step of your solution
3x - By = 7
x +2y = -7
x = - 3
y = -2
Step-by-step explanation:
3x - 8y = 7
x +2y = -7
We standardize the coefficient of one variable such that it addition will result to zero;
3x - 8y = 7
(x +2y = -7)4
Then multiply the one equation with a constant (this case 4) to get;
3x – 8y = 7
4x + 8y = - 28
We add the two equations;
3x – 8y = 7
+
4x + 8y = - 28
=
7x = - 21
x = -21 / 7
x = - 3
Now we evaluate y by replacing the value of x with -4 in one of the equation;
x +2y = -7
-3 +2y = -7
2y = -7 + 3
2y = - 4
y = -2
Learn More:
For more on linear combination check out;
https://brainly.com/question/13959574
https://brainly.com/question/12057389
#LearnWithBrainly
Three fifths of the members of a hiking club went
on the last hiking trip. It 39 people went on the
trip, how many are in the club?
There are 65 people in the club.
Step-by-step explanation:
Given,
Fraction of people went on hiking = [tex]\frac{3}{5}[/tex]
No. of people went on hiking = 39
Let,
x be the number of people at club.
According to given statement;
[tex]\frac{3}{5}\ of\ x = 39\\\\\frac{3}{5}x=39\\0.6x=39\\[/tex]
Dividing both sides by 0.6
[tex]\frac{0.6x}{0.6}=\frac{39}{0.6}\\x=65[/tex]
There are 65 people in the club.
Keywords: fractions, division
Learn more about fractions at:
brainly.com/question/1234767brainly.com/question/1238144#LearnwithBrainly
❤❤Solve for the unknown by using the additive inverse. Type the FULL answer in the box, without using any spaces (ex., X=5).
–X + 4 = –2X – 6
Answer:
35 is 51% of what number?
Answer:
68.627
Step-by-step explanation:
51%=0.51
35/0.51=68.627
Answer:
68.627 is the answer!
Step-by-step explanation: I just took a test on it like 5 minutes ago!PLEASE MARK BRAINLIEST!!!! PLEASE!!! HAVE A NICE DAY!!!!
On a coordinate plane, a solid straight line has a positive slope and goes through (negative 4, 0) and (0, 2). Everything to the right of the line is shaded. Which linear inequality is represented by the graph? y ≤ One-halfx + 2 y ≥ One-halfx + 2 y ≤ One-thirdx + 2 y ≥ One-thirdx + 2
Answer:
[tex]y\le\dfrac{1}{2}x+2[/tex]
Step-by-step explanation:
On a coordinate plane, a solid straight line has a positive slope and goes through (negative 4, 0) and (0, 2). This line has the equation
[tex]y-0=\dfrac{2-0}{0-(-4)}(x-(-4))\\ \\y=\dfrac{1}{2}(x+4)\\ \\y=\dfrac{1}{2}x+2[/tex]
The origin belongs to the shaded region, so its coordinates must satisfy the inequality. Since
[tex]\dfrac{1}{2}\cdot 0+2=2\ge 0,[/tex]
then the correct inequality is
[tex]y\le\dfrac{1}{2}x+2[/tex]
Answer:
A
y ≤ [tex]\frac{1}{2}[/tex]x + 2
Step-by-step explanation:
A restaurant manager can spend at most $400 a day for operating costs and payroll. It costs $100 each day to operate the bank and $50 dollars a day for each employee. Use the following inequality to determine how many employees the manager can afford for the day, at most: 50x + 100 ≤ 600
Answer:
The restaurant Manager can afford 6 employees for the day.
Step-by-step explanation:
Manager can spend at most of $400.
Total Money ≤ $400
Cost to operate bank = $100
Cost for each employee = $50
Let number of employees for the day be[tex]x[/tex]
Hence the equation will become;
[tex]50x + 100 \leq 400[/tex]
Solving this equation we get;
[tex]50x + 100 \leq 400\\50x \leq 400-100\\50x \leq 300\\x\leq \frac{300}{50}\\\\x\leq 6[/tex]
Hence, The restaurant Manager can afford 6 employees for the day.
Answer:
x < = 10
Step-by-step explanation:
i did it on photo math so yah
Amit built a sand castle that measured 600 centimeters by 600 centimeters, and dug a moat around it.
Afterward, he decided to change the castle size, making it 8 meters by 6 meters.
How much longer will the new moat be than the old one?
Answer:
4 meters longer.
Step-by-step explanation:
Amit built a sandcastle that measured 600 cm by 600 cm i.e. 6 meters by 6 meters.
Therefore, its perimeter is 2(6 + 6) = 24 meters
Now, afterward, he decided to change the castle size, making it 8 meters by 6 meters.
Therefore, its perimeter is 2(6 + 8) = 28 meters
Therefore, the perimeter of the new castle is increased by (28 - 24) = 4 meters.
If Amit dug a moat around his castle then the new moat will be 4 meters longer than the old one. (Answer)
As the moat is dug around the castle, its length will be the same as the perimeter of the castle.
Write in vertex form y=x^2+16x-71
Good evening ,
Answer:
x^2+16x-71 = (x+8)²-135
Step-by-step explanation:
x^2+16x-71 = (x+8)²-8²-71
= (x+8)²-(64+71)
= (x+8)²-135.
:)
Help me please with question 4 b
Answer:
see explanation
Step-by-step explanation:
The second term of sequence P is 2a + b
The third term of sequence Q is 3b + a
Equating gives
2a + b = 3b + a ( subtract a from both sides )
a + b = 3b ( subtract b from both sides )
a = 2b ← as required
Good evening ,
Step-by-step explanation:
4 (b)
The 2nd term of sequence P is 2a+b
The 3rd term of sequence Q is 3b+a
2a+b=3b+a ⇌ (2a-a) = (3b-b) ⇌ a=2b.
:)
Benjamin drove a distance of 301.5 miles in
4.5 h. If Benjamin drove at a constant rate, how
many miles per h did he drive?
Answer: 67 miles per hour
Step-by-step explanation: [tex]v = \frac{s}{t}[/tex] where v is velocity, s is space and t is time;
[tex]\frac{301.5 miles}{4.5 h}[/tex] = 67
If 6 + 2 = 8, does 6+2 +3= 8+3? Why or
why not?
Answer:
yes
Step-by-step explanation:
Because 6+ 2 equals 8 then plus 3 equals 11 and 11 equals 8+3
For apples 2 lb for $3.38 unite rate___ cost___
Answer:
1.69
Step-by-step explanation:
well to find out the unit rate that would be a pound now we need to find out how much it would cost for 1 lb which would be 3.38 / 2 which would be 1.69 as your answer
Answer:
$1.69 per pound
Step-by-step explanation:
3.38/2=1.69
There's 5 trees fill with apples. Alex wants 2 off each tree. How much apples do she have?
Answer:
10
Step-by-step explanation:
5 trees * 2 from each = 10 apples
Answer:
10
Step-by-step explanation:
5*2=10